Perancangan Aplikasi Absensi Berbasis Android Untuk Peningkatan Kinerja Karyawan pada Universitas Nasional - Satriawan Desmana; Setyawan Widyarto (Proceedings of the Informatics Conference, 2024)
The National University Universitas Nasional) is using a fingerprinting system to record the attendance of its employees, but it is not yet effective. The attendance application is used to register employees, record their attendance, search for employee data and generate attendance reports. The fingerprinting system has proved ineffective with the introduction of working from home (WFH). Online attendance recording has become a solution for recording employee attendance. The method used in this study includes research and development and the prototyping model in developing the system.